2019
DOI: 10.3390/molecules24152855
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Phytochemistry of the Cuban Endemic Medicinal Plant Phyllanthus orbicularis: Fideloside, a Novel Bioactive 8-C-glycosyl 2,3-Dihydroflavonol

Abstract: Phyllanthus orbicularis (Phyllanthaceae) is an endemic evergreen tropical plant of Cuba that grows in the western part of the island and is used in traditional medicine as an infusion. The aqueous extract of this plant presents a wide range of pharmacological activitiessuch as antimutagenic, antioxidant and antiviral effects. Given the many beneficial effects and the great interest in the development of new pharmacological products from natural sources, the aim of this work was to investigate the phytochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
0
10
0
1
Order By: Relevance
“…Two of the remaining studies did not report results from a positive control (Francioso et al, 2019; Kim et al, 2018), while Pendota et al (2018) found that the antiinflammatory activity of the glycoside tiliroside was somewhat less than that of curcumin, the positive control.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the remaining studies did not report results from a positive control (Francioso et al, 2019; Kim et al, 2018), while Pendota et al (2018) found that the antiinflammatory activity of the glycoside tiliroside was somewhat less than that of curcumin, the positive control.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, eight procyanidin C trimer isomer were identified (peaks 3, 5, 7, 8, 12, 16, 17 and 34) evaluating their molecular formula (C 45 H 38 O 18 ) and their characteristic MS/MS pattern which displayed two intense ion fragments at 287 and 407 [35] . These compounds were earlier detected in Phyllanthaceae plants [25] . Peak 4, 9 and 20 gave a molecular formula C 60 H 50 O 24 and a ion fragment at 287, 407, 575 and 863 enabling their identification as procyanidin D tetramer isomers [36] .…”
Section: Resultsmentioning
confidence: 99%
“…One C-glycosylated flavonoid, isovitexin (20), was also detected in the extracts of A. uleanus. This class of compound is found in some genera of Euphorbiaceae, such as Aleurites [38], Croton [39], Jatropha [40], and Phyllanthus [41]. One biflavonoid was also annotated as 3′′′-O-methylfukugetin (21).…”
Section: Chemophenetic Significancementioning
confidence: 99%